SARS-CoV-2 induces transcriptional signatures in human lung epithelial cells that promote lung fibrosis - Jincheng Xu; Xiaoyue Xu; Lina Jiang; Kamal Dua; Philip M. Hansbro; Gang Liu (Respiratory Research, 2020)
Abstract Background Severe acute respiratory syndrome (SARS)-CoV-2-induced coronavirus disease-2019 (COVID-19) is a pandemic disease that affects > 2.8 million people worldwide, with numbers increasing dramatically daily. However, there is no specific treatment for COVID-19 and much remains unknown about this disease. Angiotensin-converting enzyme (ACE)2 is a cellular receptor of SARS-CoV-2. It is cleaved by type II transmembrane serine protease (TMPRSS)2 and disintegrin and metallopeptidase domain (ADAM)17 to assist viral entry into host cells. Clinically, SARS-CoV-2 infection may result in acute lung injury and lung fibrosis, but the underlying mechanisms of COVID-19 induced lung fibrosis are not fully understood. Methods The networks of ACE2 and its interacting molecules were identified using bioinformatic methods. Their gene and protein expressions were measured in human epithelial cells after 24 h SARS-CoV-2 infection, or in existing datasets of lung fibrosis patients. Results We confirmed the binding of SARS-CoV-2 and ACE2 by bioinformatic analysis. TMPRSS2, ADAM17, tissue inhibitor of metalloproteinase (TIMP)3, angiotensinogen (AGT), transformation growth factor beta (TGFB1), connective tissue growth factor (CTGF), vascular endothelial growth factor (VEGF) A and fibronectin (FN) were interacted with ACE2, and the mRNA and protein of these molecules were expressed in lung epithelial cells. SARS-CoV-2 infection increased ACE2, TGFB1, CTGF and FN1 mRNA that were drivers of lung fibrosis. These changes were also found in lung tissues from lung fibrosis patients. Conclusions Therefore, SARS-CoV-2 binds with ACE2 and activates fibrosis-related genes and processes to induce lung fibrosis.